2020
DOI: 10.33549/physiolres.934393
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled and Nasal Nitric Oxide – Impact for Allergic Rhinitis

Abstract: FeNO measurement is a validated non-invasive technique, which is used for diagnosis and monitoring of asthma. It would be desirable to find a reliable method to monitor allergic rhinitis (AR) via measurement of FeNO, and/or nasal nitric oxide (nNO). The aim of our study was the assessment of the efficacy of FeNO and nNO as markers in AR treatment. FeNO and nNO were measured with the portable NO analyser (NIOX MINO®) in healthy participants and in patients with AR. The patients were examined during the pollen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…In a study performed by Martina et al who examined FeNO and nNO, gender-related differences were found in the FeNO, but not in the nNO levels neither for control nor for allergic rhinitis groups [20]. In consistent with the literature, when our patients were evaluated according to their gender, female subjects in the AR group had significantly higher nNO levels compared to those of NAR group, but no such difference was found within the groups.…”
Section: Discussionsupporting
confidence: 83%
“…In a study performed by Martina et al who examined FeNO and nNO, gender-related differences were found in the FeNO, but not in the nNO levels neither for control nor for allergic rhinitis groups [20]. In consistent with the literature, when our patients were evaluated according to their gender, female subjects in the AR group had significantly higher nNO levels compared to those of NAR group, but no such difference was found within the groups.…”
Section: Discussionsupporting
confidence: 83%
“…Individuals with allergic rhinitis (AR) frequently have co-existing asthma (estimated at 10-40%) (17), while another 45% of AR individuals without asthma have bronchial hyperresponsiveness (18), an intermediate step toward asthma development. Selected studies have observed that individuals with AR can have an abnormal pulmonary function test (PFT) (19)(20)(21)(22)(23)(24) and fractional excretion of nitric oxide (FeNO) (25)(26)(27)(28)(29) even in the absence of asthma, suggesting that pollen is an important trigger for lower airway inflammation. In addition, FeNO has been shown to increase in sensitized individuals at times of higher pollen counts (27) and has been associated with the number of positive reactions on the SPT (25).…”
Section: Study Rationale For the Six Health Outcomes Pulmonary Outcomesmentioning
confidence: 99%
“…The diagnostic values of nasal NO in allergic rhinitis were reported in various patient populations [35,58,60,73,[78][79][80]. Because the measurement of nasal NO is noninvasive, easy to perform, and economical, it has become a popular and valuable test for the diagnosis of AR even in children [81].…”
Section: Increased Inos Activities In Armentioning
confidence: 99%
“…Interestingly, products with a bitter taste that are secreted from common microorganisms are detected by the receptors of upper-airway epithelial cells. These products elicit T2R (taste family 2 bitter receptor proteins)-activated downstream responses to enhance the production of NO with bactericidal activities [ 33 , 34 , 35 ]. Bacteriostatic or bactericidal effects of NO may be species-specific.…”
Section: Nos Activities In the Human Nose And Paranasal Sinusesmentioning
confidence: 99%
See 1 more Smart Citation